2018
DOI: 10.4995/wrs.2018.7864
|View full text |Cite
|
Sign up to set email alerts
|

Growth performance and antioxidant status of growing rabbits fed on diets supplemented with Eucommia ulmoides leaves

Abstract: <p>The present study evaluated the effect of dietary <em>Eucommia ulmoides leaves</em> (EUL) on growth performance and antioxidant status of growing rabbits under heat stress condition. Four hundred and fifty weaned New Zealand male rabbits (6 wk old) were randomly divided into 3 equal groups (150 rabbits/group) and fed with a basal diet (control, digestible energy (DE): 15.92 MJ/kg and crude protein (CP): 19.24%) or the basal diet supplemented with 1 or 5 g of EUL/kg of diet (EUL1 and EUL5),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The consequences of exposure of rabbits to ambient temperature outside their thermal neutrality zone (21 to 25°C) are impaired growth, feed intake and utilisation (Brewer and Cruise, 1994;Marai et al, 2002), and heat stress is also one of the factors causing oxidative stress in the tropics (Kumar et al, 2011). Previous studies had identified the intestinal mucosa damage and increased muscle protein hydrolysis being caused by temperature-induced free radicals as the possible cause of thermal stress-induced impaired growth performance (Yuan et al, 2007;Jimoh et al, 2017, Li et al, 2018. In this study, dietary supplementation of rabbit diets with MLM at 8 or 12 g/kg caused increased average body weight gain and average daily weight gain of the rabbits when compared to the control.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The consequences of exposure of rabbits to ambient temperature outside their thermal neutrality zone (21 to 25°C) are impaired growth, feed intake and utilisation (Brewer and Cruise, 1994;Marai et al, 2002), and heat stress is also one of the factors causing oxidative stress in the tropics (Kumar et al, 2011). Previous studies had identified the intestinal mucosa damage and increased muscle protein hydrolysis being caused by temperature-induced free radicals as the possible cause of thermal stress-induced impaired growth performance (Yuan et al, 2007;Jimoh et al, 2017, Li et al, 2018. In this study, dietary supplementation of rabbit diets with MLM at 8 or 12 g/kg caused increased average body weight gain and average daily weight gain of the rabbits when compared to the control.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, the anti-inflammatory and antioxidant activities in the intestinal mucosa may result in maintenance of healthy gut morphology (Kamel, 2000), improved increased nutrient absorption and enhanced growth (Cardoso et al, 2012) as recorded in this study. Previously, Li et al (2018) reported improved daily weight gain, average feed intake in rabbits' whose diets were supplemented with 1 or 5 g/kg Eucommia ulmoides leaves, while Ayodele et al (2016) reported improved feed conversion ratio in rabbits fed on 5 or 10% alchornea leaf meal inclusion diets. However, further studies are required to study the effect of MLM on the morphology of the rabbits' intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of the different leaf meals supplementation on body weight gain (BWG), feed intake (FI) and FCR are presented in The flavonoids and phytate were reported to produce antioxidant effects (Makkar, Siddhuraju, & Becker, 2007;Middleton, Kandaswani, & Theoharides, 2000). Antioxidant effects reduce intestinal mucosa damage and muscle protein hydrolysis being caused by free radicals (Jimoh, Ewuola, & Balogun, 2017;Li et al, 2018). The phytochemicals (e.g., flavonoids and phytate) present in these leaf meals could have produced antioxidant and free radical scavenging activities to maintain the integrity of the intestinal mucosa and promote growth performance (Yuan, Chen, Zhang, & Yu, 2007).…”
Section: Composition Of the Leaf Meals And The Effect Of Leaf Mealsmentioning
confidence: 99%